An Ontological Representation of Teachers’ Roles and Competencies Required For Developing Students’ Personal Learning Environments - Ahmed Shaikh, Zaffar; Ahmed Khoja, Shakeel (INTI International University, 2011)
This paper discusses the theoretically created ontological representation of teachers’ roles and competencies required to develop students’ Personal Learning Environments (Pits) in an efficient and effective way. An ontology model is developed that shows the relationship of teachers’ roles with various stakeholders such as teachers’ required competencies, students, educational Institutes, Learning spaces, constructivist learning model, and PI.E. This is based on an in-depth review of the Literature on teachers’ socially situated competencies and roles with regard to the tasks and guidance they provide to students shape their PLEs. The review process provides an Insight of PIE research studies, constructivist learning theories, and teacher changing roles. The results of this study outline the roles that portray the importance of teacher competences as role in Planning and Design, Instruction and Learning, Communication and interaction, Management and Administration, and Use of Technology.